Causes and effects of poverty and labour exploitation in Igedeland, Benue State, Nigeria - Ufana, Matthew Paul; Ogbogo, Onah Mike; Ogbenyi, Joseph (Universitas Negeri Makassar, 2024)
Poverty is one of the major problems against development in Nigeria as in most developing countries; this has been the remote cause of almost all the social ills in the country. Poverty and labour exploitation among the Igede people of Benue State is an analysis of the causes and effects of labour exploitation and the ways of mitigating poverty and labour exploitation among the Igede people of Benue State. This study is both expository and descriptive. A sample of 440 respondents from the two Local Governments of Oju and Obi formed the sample of the study. It adopts the Labour Theory of Value by Karl Marx. The paper found out that poverty significantly influences labour exploitation; the causes of poverty and labour exploitation among the Igede people are illiteracy, marginalization, absence of social amenities, corruption, inferiority complex and unemployment. The effects include migration, economic dependence, high death rate, depression and vulnerability. The ways of mitigating poverty and labour exploitation among the Igede people of Benue State are good governance, wealth creation, employment opportunities and improvement in illiteracy level.